السينما في الجزائر (1895-1990م) - أحلام مخلوفي; د/عبد الرحمان قفاف (جامعة عمار ثليجي الاغواط, 2023)
الملخص: تعتبر السينما من أهم أشكال التعبير الجديدة ، لأنها استطاعت خلال فترة وجيزة أن تضع نفسها ضمن أشكال الفن الحديث ، واعتمدت في إنتاجها الفني والإعلامي على موضوعاته المقدمة بكل قوته. انطلاقا من أهمية هذا الأخير ، يدور السؤال الإشكالي حول استغلال فرنسا لإدامة مفهوم الاستعمار وطريقة تدويله وتوثيقه للمسألة الجزائرية. انطلاقا من التقدم نواجه الحقائق التالية: أن السينما الجزائرية لعبت دورا هاما في التوجه السياسي والأيديولوجي ،واجتياحها للشعوب بطريقة جديدة ، فالأمر متروك لنا لرصد التوجه في السياسة الاستعمارية التي تزامنت مع ظهور السينما في الجزائر منذ عام 1895 م ، وكانت مصدر الأعمال السينمائية، حيث كانت الموضوعات الثورية للسينما جديرة بالتقدير ومبتكرة،رغم الظروف الصعبة التي يعيشها صناع الفيلم ،وبسبب النجاح الباهر الذي حققته الأفلام ، انطلقت ثورة التحرير لتوثيقها من أجل قضاياها. Summary: Cinema is considered one of the most important new expressive arts, as it was able in a short time to position itself within themodern art forms, and it relied on its artistic and media production on its topics presented with full force. Based on the importance of the latter, the problematic issue revolves around the exploitation of France to perpetuate the concept of colonialism and how it was internationalized and documented for the Algerian issue. Based on the progress, we find ourselves facing the following facts: that Algerian cinema played an important role in politics and ideological orientation and its invasion of peoples in a new way, so it comes to us to monitor the orientation in colonial politics, which coincided with the emergence of cinema in Algeria since 1895 AD, and was the source of cinematic works . Where cinema's revolutionary themes were meritorious and innovative,Despite the difficult circumstances experienced by the filmmakers, and because of the outstanding success achieved by the films, the liberation revolution was launched to document them for the sake of their causes.